A CLINICAL COMPARATIVE STUDY ON THE HEALING EFFICACY OF NANO SILVER AND BETADINE IN DIABETIC FOOT ULCERS - KALANGRI MURALI KRISHNA,; KALANGARI SWATHI,; UDATHA NIRMALA, (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of the study was to study the efficacy of topical agents like betadine solution and nano silver solution/gel in the management of diabetic foot ulcer. Materials: The study was a prospective, parallel-group, comparative trial. The patients were admitted with diabetic foot ulcer for a period of 2 years. A comparative study was done between both groups regarding the time of healing. Number of dressings and reduction of ulcer size was monitored. The number of patients included in our study was 60 out of which 30 were in test group with betadine solution and 30 were in another test group with nano silver solution. Results: Age distribution, 25 patients are between 51 and 60 years of age. In sex distribution, males are affected more than females. In mode of onset, 68.75% of ulcers are traumatic in onset; plantar aspect and forefoot are most. Blood sugar levels between 200 and 300 mg% are in 38.33% of patients. Patients receiving insulin were 7l.66%, which helped in good glycemic control. Average duration of hospital stay is less with test Group l, that is, 30 patients stay. Percentage reduction of ulcer is between 91 and 99%, in 27 patients of test Group l While only six patients in test Group 2 had 91–99% reduction in ulcer size with p=0.00 and is highly significant, number of dressings required per patient are l0.225±2.957 in test group and are 21.65±3.847 in test Group 2, p=0.00 and significant. Conclusions: Thus using nano silver dressings in the treatment of diabetic foot ulcers is found to be safe, effective, promoter of wound healing promote epithelization, and accelerates healing. Eliminates anaerobes and breaks microbial synergy more effectively than simple betadine dressing. Hence, nano silver gel proves to be more effective in the management of diabetic foot ulcer.